2010
DOI: 10.1523/jneurosci.3077-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Medial Parietal Cortex Encodes Perceived Heading Direction in Humans

Abstract: The ability to encode and update representations of heading direction is crucial for successful navigation. In rats, head-direction cells located within the limbic system alter their firing rate in accordance with the animal's current heading. To date, however, the neural structures that underlie an allocentric or viewpoint-independent sense of direction in humans remain unknown. Here we used functional magnetic resonance imaging (fMRI) to measure neural adaptation to distinctive landmarks associated with one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
114
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(147 citation statements)
references
References 26 publications
14
114
2
Order By: Relevance
“…Head direction cells have also been observed in the rodent RSC (Chen et al, 1994;Cho and Sharp, 2001), suggesting that this region could support tracking head orientation. Recent human neuroimaging studies have indicated the RSC integrates self-motion cues during navigation with routebased spatial information (Wolbers and Buchel, 2005), directs movement towards a goal location (Epstein, 2008), and is sensitive to heading direction (Baumann and Mattingley, 2010;Marchette et al, 2014). Functional connections found here between optic flow sensitive regions and the RSC further establish a role for the RSC in updating position and orientation based on visual cues from optic flow.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Head direction cells have also been observed in the rodent RSC (Chen et al, 1994;Cho and Sharp, 2001), suggesting that this region could support tracking head orientation. Recent human neuroimaging studies have indicated the RSC integrates self-motion cues during navigation with routebased spatial information (Wolbers and Buchel, 2005), directs movement towards a goal location (Epstein, 2008), and is sensitive to heading direction (Baumann and Mattingley, 2010;Marchette et al, 2014). Functional connections found here between optic flow sensitive regions and the RSC further establish a role for the RSC in updating position and orientation based on visual cues from optic flow.…”
Section: Discussionsupporting
confidence: 56%
“…During FPP navigation compared with the ITI, increased functional connectivity was observed between regions of the brain that are sensitive to optic flow motion and the retrosplenial cortex, posterior parietal cortex, hippocampus, and medial prefrontal cortex, which are brain regions previously noted in human navigational studies (Wolbers et al, 2007;Spiers and Maguire, 2007;Brown et al, 2010;Baumann and Mattingley, 2010;Doeller et al, 2010;Brown and Stern, 2014;Sherrill et al, 2013). For a summary of all brain regions showing significant functional connectivity with V3A, V6, and hMT+ seed regions at the whole-brain level for FPP navigation, see Tables 1, 2, and 3, respectively.…”
Section: Functional Connections With Optic Flow Sensitive Regions Durmentioning
confidence: 68%
“…In humans, neuroimaging and neuropsychological work suggests that place recognition is primarily mediated by the parahippocampal place area (PPA), a region of medial occipitotemporal cortex that responds strongly when subjects view environmental scenes or landmark objects (21-23), whereas heading retrieval is primarily mediated by a system centered around the retrosplenial complex (RSC) in the medial parietal lobe (24)(25)(26)(27)(28). Analogous to the current findings, the PPA appears to be sensitive to both geometric and nongeometric information (22,(29)(30)(31)(32)(33), whereas RSC appears to be especially sensitive to geometry when people retrieve spatial information from memory (28).…”
Section: Discussionmentioning
confidence: 99%
“…Since many of the traditionally thought unimodal neural circuits recently turn out to be multimodal, one hypothesis might be that the neural mechanism for whole-body navigation in the ambulatory space might perform also tactile path integration in the manipulatory space. In addition to the hippocampus and the entorhinal cortex, the medial and the posterior part of the parietal cortex, which are involved in somatosensory processing, spatial orientation, and navigation [37][38][39], might be good candidates as neuroanatomical substrate.…”
Section: Discussionmentioning
confidence: 99%